Psoriasis, epidemiology, etiopathogenesis, clinical presentation, treatment – a systematic review - Ryszkowski, Maksymilian; Fornal, Krystian; Będkowska-Kuśmierek, Natalia; Zaborowska, Sabina; Pawlak, Paulina; Wojcieszuk, Olaf; Starczewski, Łukasz; Babik, Adrianna; Kamińska, Kamila; Będkowska-Kuśmierek, Matylda (Quality in Sport, 2026)
Introduction: Psoriasis is a chronic, relapsing, systemic inflammatory disease with an immunological basis and a strong genetic predisposition, affecting approximately 1–3% of the population. Its pathogenesis involves dysregulated immune responses with activation of T lymphocytes and overproduction of proinflammatory cytokines such as IL-17, IL-23, and TNF-α, leading to excessive keratinocyte proliferation. The disease has a multisystem character and is frequently associated with psoriatic arthritis, cardiovascular diseases, metabolic disorders, and depression. Aim: The aim of this study was to review current literature on the epidemiology, etiopathogenesis, clinical presentation, and contemporary treatment of psoriasis, with particular emphasis on its systemic nature and associated comorbidities. Conclusions: Psoriasis is a complex chronic disease requiring an individualized therapeutic approach. The severity and duration of skin lesions are associated with an increased risk of systemic complications, particularly cardiovascular and metabolic disorders. The development of biologic agents and small-molecule therapies has significantly improved treatment effectiveness and patients’ quality of life. Effective management should include both control of cutaneous symptoms and treatment of comorbid conditions. Keywords: psoriasis; epidemiology; etiopathogenesis; clinical presentation; treatment; comorbidities; biologic therapy; systemic inflammation.